2020
DOI: 10.25156/ptj.v10n1y2020.pp140-147
|View full text |Cite
|
Sign up to set email alerts
|

Time History Analysis of Frame Structure Systems by State-space Representation Method

Abstract: This paper develops the state-space representation (SSR) in the field of seismic analysis of the building structures. Dynamic analysis of multi-degree-of-freedom structures involves the solution of second-order linear differential equations which they represent the equation of motion of the structure. In this paper, a SSR was formulated to replace differential equation with two coupled first-order linear differential equations. The objectives of this study are as follows: (i) To implement the SSR as a powerful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
0
0
Order By: Relevance
“…Many studies confirmed that the state-space method has both accuracy and short time advantages that significantly reduce the cost of the analysis [4,2]. Due to that, it used in many domains, mentioning the analysis of vibration of car seat using passive and semi active dampers [5].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies confirmed that the state-space method has both accuracy and short time advantages that significantly reduce the cost of the analysis [4,2]. Due to that, it used in many domains, mentioning the analysis of vibration of car seat using passive and semi active dampers [5].…”
Section: Introductionmentioning
confidence: 99%